Mangrove Plant Community Structure, Sungai Apung Village, Tanjung Balai Sub-District, Asahan District, North Sumatra Province - Sitio, Lista Celsi Wilda; Barat, Welmar Olfan Basten; Retno, Ria (Journal of Applied Geospatial Information, 2023)
Mangroves are a type of vegetation found in tropical coastal areas. In general, mangrove vegetation thrives in sloping coastal areas or near river estuaries and beaches that are protected from waves. The physical function of mangrove forests is to keep the coastline stable, protect the coast from erosion, reduce storms and waves, and catch sediment, while the biological function of mangroves is as a spawning place or residence, shelter for shrimp, crabs, shellfish, and other animals. Research on Mangrove Plant Community Structure in the Kwala Indah Village Area was carried out in August–November 2023 with the aim of determining mangrove types, mangrove diversity and uniformity, dominance, the Important Value Index (INP), and mangrove canopy cover in Singai Apung Village. The method used to observe the community structure of mangrove plants is to use the quadrant transect method by analyzing species density, relative density, species frequency, relative frequency, species dominance, relative dominance, and important value index at the tree level. , saplings and seedlings, as well as canopy cover. Based on the research results, 10 species were found, namely Avicennia alba, Avicennia lanata, Bruguiera cylindrica, Bruguiera sexangula, Excoearia agallocha, Lumnitzera littorea, Rhizophora apiculata, Rhizophora mucronata, Sonneratia alba, and Xylocarpus granatum. Rhizopora mucronata, which has INP, diversity in the medium category, and uniformity in the high category, has the highest dominance in Rhizophora mucronata. Canopy cover is in the dense category.